Co-Learning on Budget Literacy and Expenditure Tracking of the Village Development Program - Hidayat, Rahmad; Tauhid; Sauki, Muhammad (Ilin Institute, 2022)
At the village level, not all residents have knowledge of the content of budget documents as well as minimal attention and awareness to influence the budgeting process that takes place in their area. Based on these problems, this activity is oriented towards increasing budget literacy and the ability to trace expenditures for village development programs to certain community groups. Partners are trained in a targeted manner so that they can map the weaknesses and strengths of the village budgeting posture as seen in the current year's APBDesa document, both in its structure, format, and allocation as a basis for advocating for their priority needs to the Village Government and BPD so that they can be accommodated in the village planning-budgeting document in future. This activity has been implemented on February 21, 2021, at 08.00-11.00 PM in the Office Hall of Rabakodo Village, Woha District, Bima Regency, West Nusa Tenggara Province by involving twenty-five people from the vulnerable group which consisted of housewives, poor people, and young villagers. Pedagogical approaches used to teach budget literacy and expenditure tracing were the combination of direct instruction with enquiry-based learning, values clarification exercises, and participatory learning. This intervention was effective to increase the participants' knowledge and insight into the participatory budgeting process. Nevertheless, their attention and awareness to participating in the formulation of the village budget and monitoring its spending need to be forged further through several similar facilitations.